Effect of Bransford & Stein Model on Developing Scientific Thinking of Literary Fifth Grade Students in The Subject of History - Obaid, Wissam Aziz; Abbas, Zaid Alwan (International Journal of Psychosocial Rehabilitation, 2020)
This research aimed to identify the effect of Bransford and Stein model on developing scientific thinking of literary fifth-grade students in the subject of history. To achieve this, the two researchers adopted the experimental design with post- test , the sample was a preparatory school for boys from the schools in the General Directorate of Al-Qadisiyah Education, the sample reached (54) students 27 for each group, the researchers formulated (175) behavioral objectives based on Bloom’s classification of behavioral objectives, as they prepared (16 ) educational plans for each of the two groups, the researchers prepared a test to measure scientific thinking of (30) items divided into five domains (6 items) for each domain , its validity and reliability were confirmed , the two groups were equivalent in variables (age, intelligence, parents’ achievement level , previous achievement of history ), the experiment applied in the first course of the academic year (2019-2020). SPSS was used to extract the results. A statistically significant difference was found in favor of the experimental group that studied by Bransford & Stein model.